Kemandirian Literasi Pada Guru Melalui Pembuatan Perpustakaan Digital Berbasis Desain - Muttaqin, Islakhul; Puspita, Pandini Dwi; Lubis, Siti Halida; Nur Anganthi, Nisa Rachmah (Universitas Muhammadiyah Surakarta, 2023)
Digital libraries are one of the implementations of information technology development. So far, both government and private institutions have developed many digital libraries, either in the form of websites or Android-based applications that can be accessed through various devices. However, at present, all elementary schools in Sukoharjo District do not have digital libraries for literacy self-sufficiency. Therefore, this community service aims to provide assistance related to the creation of digital libraries. The community service is conducted through direct simulation, where facilitators provide tutorials followed by the participants. The main objective of this service is to encourage teachers in elementary schools in Kartasura Sub-district, Sukoharjo, to be creative in developing educational media. This digital library, based on design, utilizes applications like Canva for design, Google Drive for storage, and the BSE (Educational Materials Center) catalog from the Ministry of Education and Culture as the main training materials. Fifteen teachers from various elementary schools in Kartasura Sub-district participated in the training, and the response was positive. Participants implemented the results of the training in their respective schools. Furthermore, this digital library serves as a means to fulfill the needs of seeking reference sources, such as books, magazines, encyclopedias, and other reading materials that support the teaching and learning process. Through this training, literacy self-sufficiency is fostered among schools, teachers, and students.